Training induced changes in external load on academy soccer players - Jordan, A.; Thomas, A.; Wilkie, B.; Harper, D.; Liefieth, A.; Metcalfe, M. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: A combination of GPS and accelerometry data can quantify the external load experienced by an athlete to analyse performance and monitor training load. The aim of this study was to determine the effect of a training intervention on external load and sportspecific fitness in soccer players. Methods: Nine Academy soccer players (age 17 ± 1, height 1.76 ± 0.84 m and mass 68.3 ± 7.5 kg) completed a 6-week gym- (2x1 hours per week) and field-based training intervention (2x1 hours per week) with a focus on eccentric and deceleration exercises. Pre and post-intervention measures of anaerobic capacity were determined by a Triple 120 m test (Holloway et al., 2008) modified for soccer players. The modified T120 consisted of 3 bouts of 12 x 10 m shuttle sprints with a chest-to-floor drop and 5 toe-taps on the 1st, 5th and 9th shuttle. Bouts were separated by 1 minute low intensity active recovery. Players wore GPS and accelerometer monitors (Catapult Optimeye S5) during the tests. Time to complete modified T120, average bout time, Player Load (external load) and Player Load/min were calculated (recovery periods excluded from all parameters). Results: Paired t-tests identified significant reductions in the time to complete the modified T120 (119.91s to 116.96s, p=0.033), mean time per bout (39.97s to 38.99s, p=0.033) and Player Load (54.4 to 52.6, p=0.045) following the intervention. Discussion: The reduced external load is indicative of an improved economy of movement during the modified T120. Potentially, the load associated with accelerating and decelerating during the modified T120, which are physically demanding actions and key determinants of soccer performance (Osgnach et al., 2010), might have been reduced following training. This is likely due to improved damping of ground reaction forces through the lower limb as a result of eccentric training. The reduced external load is particularly interesting given the faster performance of the modified T120 test observed. This is in agreement with Akenhead et al., (2013) who previously observed reduced PL at constant pace following training. This study provides a basis for assessing external load alongside variations in physical performance and internal load.